Mapping brain volumetric abnormalities in never-treated pathological gamblers. Issue 3 (30th June 2015) - Fuentes, Daniel; Rzezak, Patricia; Pereira, Fabricio R.; Malloy-Diniz, Leandro F.; Santos, Luciana C.; Duran, Fábio L.S.; Barreiros, Maria A.; Castro, Cláudio C.; Busatto, Geraldo F.; Tavares, Hermano; Gorenstein, Clarice
Abstract: Several magnetic resonance imaging (MRI) studies to date have investigated brain abnormalities in association with the diagnosis of pathological gambling (PG), but very few of these have specifically searched for brain volume differences between PG patients and healthy volunteers (HV). To investigate brain volume differences between PG patients and HV, 30 male never-treated PG patients (DSM-IV-TR criteria) and 30 closely matched HV without history of psychiatric disorders in the past 2 years underwent structural magnetic resonance imaging with a 1.5-T instrument. Using Freesurfer software, we performed an exploratory whole-brain voxelwise volume comparison between the PG group and the HV group, with false-discovery rate correction for multiple comparisons ( p <0.05). Using a more flexible statistical threshold ( p <0.01, uncorrected for multiple comparisons), we also measured absolute and regional volumes of several brain structures separately. The voxelwise analysis showed no clusters of significant regional differences between the PG and HV groups. The additional analyses of absolute and regional brain volumes showed increased absolute global gray matter volumes in PG patients relative to the HV group, as well as relatively decreased volumes specifically in the left putamen, right thalamus and right hippocampus (corrected for total gray matter). Our findings indicate that structural brain abnormalities may contribute to the functional changes associated with the symptoms of PG, and they highlight the relevance of the brain reward system to the pathophysiology of this disorder. Highlights: Structural MRI compared brain volumes of pathological gamblers (PG) and healthy volunteers (HV). Voxelwise analyses showed no clusters of significant regional differences between PG and HV. Region of interest analyses showed lower left putamen and right thalamus/hippocampal volumes in PG.